The Effect of Supervision Consultant Performance on the Implementation Quality of the National Road Construction - Kartono Wibowo; Muhamad Adhar; Fauzy Fachruddin (Universitas Islam Sultan Agung, 2022)
The performance of supervision consultants in determining the project’s success is influenced by the quality of implementation. This quality is often the main focus in construction because it plays a central role in project performance. This research was conducted to identify several factors and their influence on the performance of the supervision consultant in the case of national road construction. This study belonged to a descriptive case study. Data of the study were collected by distributing questionnaires to the officers of the Public Works Department of Highways, the Implementing Contractors, and the Supervision Consultants. In total there were 58 respondents randomly selected to get involved in the study. Regression analysis was performed on the data obtained by using SPSS software version 17. The results of the study indicated there are several performance factors of the supervision consultant, that simultaneously affect the implementation quality of the national road construction. The factors of supervision consultants which partially influenced the implementation quality of the national road construction, if reviewed respectively based on the order were (1) field attendance (1.851); (2) Work Experience (1,613); (3) Supervision officers (1.467); and (4) planning (0.854).